ANALISIS HUKUM CRYTOCURRENCY KAJIAN FIQH DAN FATWA-FATWA DI LUAR NEGERI - Mufatzizah, Maranda Sukma (Universitas Muhammadiyah Surabaya, 2023)
Cryptocurrency is the first application of blockchain technology, but the potential of this technology is not limited to the monetary system and its widespread adoption is still a worldwide topic causing many countries to hide this cryptocurrency. Here the author tries to assess crypto assets based on studies of fikih and fatwa abroad. In this study the authors used sociological legal research, this research method serves to see the law in a real sense and examine how the law works in society. To analyze existing theories, this study uses a conceptual approach to analyze existing theories so that solutions to legal problems can be found. The results in this study are that there are two thoughts, the first school of thought argues that cryptocurrencies can be used for payments, remittances, and storing assets as long as users know in detail the types of cryptocurrencies, the second opinion is prohibited in the eyes of Sharia because of excessive risks for individuals, countries and no clear laws. conclusions in this study. In the view of fikih scholars who allow it to refer to the understanding that fluctuations in crypto are not classified as gharar, especially for people who have cryptocurrency knowledge. from the results of the fatwa analysis of the permissibility of cryptocurrency, namely in Malaysia, LBM PWNU Yogyakarta Indonesia and in China in accordance with the fatwa and legal provisions, while those that prohibit it are in Middle Eastern countries and LBM PWNU East Java Indonesia.Keywords: Cryptocurrency, Fikih and Fatwa Studies